ANALISIS HUKUM PASAL 37 AYAT (5) UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 DALAM PERSPEKTIF AMANDEMEN TERHADAP KONSTITUSI DI INDONESIA - Min Amir Habib Efendi Pakpahan; Dessy Artina; Zulwisman Zulwisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
The existence of Article 37 paragraph (5) of the 1945 Constitution of the Republic ofIndonesia becomes interesting to be discussed in the academic space due to its contents whichmaintain the form of a unitary state as something that cannot be changed (unmendable provision).The formulation of these norms was actually inseparable from the historical aspects that colored themystical atmosphere (gestlichen hintergrund) at that time, starting from the BPUPKI session whichexpressed the views of various figures to the meeting to amend the 1945 Constitution of theRepublic of Indonesia which was amended four times from 1999-2002. Therefore, regarding theform of the state which is basically a great topic that is debated, it needs sufficient attention bothfrom an academic and legal perspective. This has become a special interest for the author toconduct further research on it.This research is a normative legal research. This is based on library research which takesquotations from reading books, or supporting books that are related to the problem to be studied.Primary, secondary and tertiary data sources are characteristic of this study. This study also usesqualitative data analysis and produces descriptive data.From the results of the research conducted, there are several conclusions obtained, namely:First, the formulation of article 37 paragraph (5) of the 1945 Constitution of the Republic ofIndonesia is only a political resultant that can be changed according to the agreement and will ofthe wider community. The interpretation of the constitution that has been carried out has succeededin describing that there are various historical and sociological factors in maintaining the form of aunitary state as the choice of the form of state that we adopt. Second, the perspective of changingthe constitution carries a juridical and theoretical implication that the term clause that cannot bechanged is only a political resultant, therefore, making it final and absolute and cannot be changedis a violation of the will of the constitution which is amended based on the will of the people.Therefore, the history of law becomes the rationale for describing and contextually explaining whythe form of the state cannot be changed. Efforts to amend the constitution should not recognize theterm finality for something that cannot be changed and contested. This can happen as long as thepublic wants it.Keywords: Constitutional Amandement – Unamandable Provision